Validity of referral hospitals for the toxicovigilance of acute poisoning in Sri Lanka - L Senarathna; NA Buckley; SF Jayamanna; PJ Kelly; MJ Dibley; AH Dawson (The World Health Organization, 2012)
OBJECTIVE: To identify the hospital admission data set that best captures the incidence of acute poisoning in rural Sri Lanka. METHODS: Data were collected on all acute poisoning cases admitted to 34 primary and 1 referral hospital in Anuradhapura district from September 2008 to January 2010. Three admission data sets were compared with the "true" incidence of acute poisoning to determine the systematic bias inherent to each data set. "True" incidence was calculated by adding all direct admissions (not transfers) to primary hospitals and to the referral hospital. The three data sets were: (i) all admissions to primary hospitals only; (ii) all admissions to the referral hospital only (direct and referrals), and (iii) all admissions to both primary hospitals and the referral hospital ("all admissions"). The third is the government's routine statistical method but counts transfers twice, so for the study transferred patients were counted only once through data linkage. FINDINGS: Of 3813 patients admitted for poisoning, 3111 first presented to a primary hospital and 2287 (73.5%) were later transferred to the referral hospital, where most deaths (161/177) occurred. All data sets were representative demographically and in poisoning type, but referral hospital data yielded a more accurate case-fatality rate than primary hospital data or "all admissions" data. Admissions to primary hospitals only or to the referral hospital only underestimated the incidence of acute poisoning by about 20%, and data on "all admissions" overestimated it by 60%. CONCLUSION: Admission data from referral hospitals are easily obtainable and accurately reflect the true poisoning incidence.